(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The research aimed to study the effect of coworkers’ interrelationships on the intention to continue and stay at work. The researcher used the case study approach and applied the research on all workers at the National Institute of Public Administration in Damascus, and the research sample was 47 workers from all functional categories and administrative levels. Data was collected from respondents by a questionnaire prepared for this purpose. Descriptive analysis of and simple regression equation were used. The research has conducted to a set of results, the most important of which are: - There is a positive attitude of the institute’s employees towards co-workers’ relationships. - The presence of a high level of intention to stay in the work among institute’s employees. - There is a significant effect of the institute’s employees’ attitudes towards co-workers’ relationships in the intention to stay at work.